(untitled) (Student’s Journal of Health Research Africa, 2023)
Introduction: The small and large intestines constitute a significant portion of the gastrointestinal tract. Numerous benign, malignant, and congenital disorders manifest from this anatomical region. Benign aetiologies primarily encompass inflammatory and infectious pathologies. The colon represents the predominant anatomical location for the occurrence of gastrointestinal neoplasia within Western populations. Aim: In order to ascertain the pattern, frequency, and location of non-neoplastic lesions impacting the intestine, with the aim of increasing clinicians’ awareness of their occurrence within this particular region. Methods: A comprehensive analysis was conducted on a total of 500 nonneoplastic gastrointestinal tract (GIT) lesions. The histopathological findings were meticulously examined, in conjunction with an analysis of the spatial distribution of lesions, and a correlation was established between the histopathological findings and the clinical parameters. Results: The predominant type of specimens obtained for analysis consisted of bowel resection samples, accounting for 433 cases (86.68% of the total). The remaining specimens were comprised of endoscopic biopsies, totaling 66 cases (13.33%). Non-neoplastic lesions were found to be more prevalent, accounting for 125 cases (83.33%), compared to neoplastic lesions, which accounted for 83 cases (16.67%). Conclusion: The meticulous evaluation of specimens, both at a macroscopic and microscopic level, in conjunction with relevant clinical data, serves as a valuable approach to achieving precise objectives and enhancing the patient’s overall well-being. Recommendation: Lesions that are not considered malignant need to be followed up every year or every two years with the help of EUS or endoscopy to rule out malignancy.